Prognostic Value of Gamma-Glutamyltransferase in Male Patients With Idiopathic Pulmonary Arterial Hypertension - Lu, Gang-Hua; Gong, Su-Gang; Li, Chao; Zhao, Qin-Hua; Jiang, Rong; Luo, Ci-Jun; Wang, Lan; Zhang, Rui (Frontiers in Cardiovascular Medicine, 2020)
The elevated gamma-glutamyltransferase (GGT) activity was regarded as an indicator of cardiovascular disease, with males having higher values than females. The greater incidence of idiopathic pulmonary arterial hypertension (IPAH) was observed in women, whereas prognosis was poor in men. The influence of GGT and its potential role in male IPAH patients have not been investigated. Serum GGT levels were measured in 338 consecutive adults IPAH patients who underwent bone morphogenetic protein receptor type 2 (BMPR2) genetic counseling, matched with healthy subjects by sex and age. The followed interval was 48±34 months. Increased serum GGT levels were more common in patients with IPAH than controls (p<0.001). Also, GGT values were significantly higher in male patients than those of females (p<0.001), further increased in male patients with carried BMPR2 mutation than those of females (p=0.002). Higher GGT levels were associated with worse hemodynamics and N-terminal pro B-type natriuretic peptide. Male patients with a GGT concentration≥53U/L had a worse survival than those of female (p=0.008). However, if GGT concentration<53U/L, there was no survival difference in genders (p=0.870). After adjustment for clinical features and heamodynamics, baseline higher GGT levels remained increased risks of all-cause mortality in males rather than females. During rehospitalization follow-up, male patients still had significantly higher values of GGT than females (p=0.010). Increased GGT levels were correlated with BMPR2 mutation, hemodynamic dysfunction and poor outcomes in male patients with IPAH. Further studies are needed to explain the origin of abnormal GGT and its potential pathogenesis in men.